Development of Diving and Snorkeling Ecotourism Based on Natural Resources Potential of on Miang Island Kutai Timur Regency - Wilson Titro Sagala; Zairion Zairion; Fredinan Yulianda (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
Miang Island has potential coral reef resources that can be used for marine ecotourism of diving and snorkeling, but there has not been any related study yet. This study aims to analyze the condition of coral reef resources, analyze the suitability and carrying capacity of the area for ecotourism and develop a strategy for developing diving and snorkeling ecotourism on Miang Island. The method being used for coral reef data collection by Underwater Photo Transect and reef fish using the Underwater Visual Census method. To develop the strategy of developing ecotourism is analyzed by using the Interpretative Structural Modeling (ISM) method. The results showed that the condition of coral reefs on Miang Island was in the moderate category with 40% live coral coverage. The area that can be used for snorkeling tours is 24.39 ha with a carrying capacity of 976 tourist visits/day. Meanwhile, the area that can be used for diving tourism is 13.40 ha with the ability to receive visitation of 536 tourist visits/day. Based on these conditions, the ecotourism development strategy is formulated that protects and utilizes coral reef ecosystems as sustainable tourism objects, facilitates access to development capital, makes a consistent policy, and coordinates between related agencies.